Stress Management Methods for Employees of the Engineering Enterprise of the Russian Industrial Complex - Tikhonov, Aleksey Ivanovich; Mikhaylov, Adrian Alekseevich; Solimene, Umberto (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article is devoted to the problem of stress management in the employees of the Russian industrial complex. The results of a study conducted at a machine-building plant located in the Urals (Russia) are presented. On the example of the basic organization, the authors conducted sociological and economic studies, identified stress or conflict situations that cause stress in the employees of the enterprise. The research is systematized the most typical stressors for the main staff and proposed a scientifically-based set of measures to reduce the identified stress - factors.